Dirk Pitt : Treasure - Book 10 - Cussler, Clive (New York : Pocket Books, 2011)
A conspiracy of evil reaches from the Arctic Circle to Tierra del Fuego, involving a violent rise of fundamentalism in Mexico and Egypt that has the U.S. captive in its own borders. Dirk Pitt is determined to find the ancient books from the library of Alexandria.
Keywords: Pitt, Dirk -- (Fictitious character) -- Fiction; Treasure troves -- Greenland; Fiction; Terrorists -- Fiction; Greenland -- Fiction; United States -- History; Invasions; Fiction; Alexandria (Egypt) -- Antiquities; Fiction